Enhancing junior high school students’ self-compassion through Two Stay Two Stray (TSTS) technique: A school-based intervention study - Zuanda, Natalia; Tanjung, Romi Fajar (Asatiza: Jurnal Pendidikan, 2025)
This study investigates the effectiveness of classical guidance and counseling services in enhancing self-compassion among junior high school students using the Two Stay Two Stray (TSTS) technique. Employing a quantitative pre-experimental design with a one-group pretest-posttest approach, the research addresses constraints in scheduling by utilizing other subjects’ class hours. The population comprised 125 students, with a sample of 22 selected through simple random sampling. The chosen class exhibited low self-compassion levels, characterized by self-judgment and isolation, based on preliminary observations. Data were collected using an instrument adapted from Kristin Neff’s self-compassion scale, measuring three key aspects: self-kindness, common humanity, and mindfulness. SPSS 22 analysis revealed normal distribution of data (pretest *p* = .376; posttest *p* = .406), confirming parametric test assumptions. The findings highlight the potential of integrating TSTS into classical counseling to foster self-compassion in adolescents—a critical skill for navigating life’s challenges. This study contributes an innovative intervention model and serves as a reference for developing evidence-based strategies in school counseling.